EffectiveNess of a multimodal preHAbilitation program in patieNts with bladder canCEr undergoing radical cystectomy: protocol of the ENHANCE multicentre randomised controlled trial. Issue 3 (7th March 2023) - Akdemir, Emine; Sweegers, Maike G; Vrieling, Alina; Rundqvist, Helene; Meijer, Richard P; Leliveld-Kors, Annemarie M; van der Heijden, Antoine G; Rutten, Vera C; Koldewijn, Evert L; Bos, Siebe D; Wijburg, Carl J; Marcelissen, Tom A T; et al.
Abstract : Introduction: Radical cystectomy (RC) is the standard treatment for patients with non-metastatic muscle-invasive bladder cancer, as well as for patients with therapy refractory high-risk non-muscle invasive bladder cancer. However, 50–65% of patients undergoing RC experience perioperative complications. The risk, severity and impact of these complications is associated with a patient's preoperative cardiorespiratory fitness, nutritional and smoking status and presence of anxiety and depression. There is emerging evidence supporting multimodal prehabilitation as a strategy to reduce the risk of complications and improve functional recovery after major cancer surgery. However, for bladder cancer the evidence is still limited. The aim of this study is to investigate the superiority of a multimodal prehabilitation programme versus standard-of-care in terms of reducing perioperative complications in patients with bladder cancer undergoing RC. Methods and analysis: This multicentre, open label, prospective, randomised controlled trial, will include 154 patients with bladder cancer undergoing RC. Patients are recruited from eight hospitals in The Netherlands and will be randomly (1:1) allocated to the intervention group receiving a structured multimodal prehabilitation programme of approximately 3–6 weeks, or to the control group receiving standard-of-care. The primary outcome is the proportion of patients who develop one or more grade ≥2 complications (according to the Clavien-Dindo classification) within 90 days of surgery. Secondary outcomes include cardiorespiratory fitness, length of hospital stay, health-related quality of life, tumour tissue biomarkers of hypoxia, immune cell infiltration and cost-effectiveness. Data collection will take place at baseline, before surgery and 4 and 12 weeks after surgery. Ethics and dissemination: Ethical approval for this study was granted by the Medical Ethics Committee NedMec (Amsterdam, The Netherlands) under reference number 22–595/NL78792.031.22. Results of the study will be published in international peer-reviewed journals. Trial registration number: NCT05480735 .